2019
DOI: 10.3390/nu11071606
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Intake and Health

Abstract: There are striking inequities in calcium intake between rich and poor populations. Appropriate calcium intake has shown many health benefits, such as reduction of hypertensive disorders of pregnancy, lower blood pressure particularly among young people, prevention of osteoporosis and colorectal adenomas, lower cholesterol values, and lower blood pressure in the progeny of mothers taking sufficient calcium during pregnancy. Studies have refuted some calcium supplementation side effects like damage to the iron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
224
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 275 publications
(236 citation statements)
references
References 101 publications
3
224
3
6
Order By: Relevance
“…The increase in hip fractures and myocardial infarct described in some studies performed in older populations with adequate basal calcium intake are still in debate [76,77]. Calcium supplementation randomized controlled trials conducted in younger populations with low basal calcium intake have shown many benefits and report no clear deleterious effects [16]. There is scarce information about high-quality clinical trials evaluating the effect of increasing calcium intake through dietary interventions in populations with low basal calcium intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in hip fractures and myocardial infarct described in some studies performed in older populations with adequate basal calcium intake are still in debate [76,77]. Calcium supplementation randomized controlled trials conducted in younger populations with low basal calcium intake have shown many benefits and report no clear deleterious effects [16]. There is scarce information about high-quality clinical trials evaluating the effect of increasing calcium intake through dietary interventions in populations with low basal calcium intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, new evidence merits reviewing these values. Nevertheless and despite the potential variation in the recommendations, most LMICs do not even reach the lower recommended levels [16]. In addition, any recommendation to introduce a calcium fortification strategy should take into account the basal calcium intake of the population and the gap to achieve the recommended levels, particularly in view of the strong differences in calcium intake between HICs and LICs [1,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Indonesia, Southeast Asia's most populous country, average calcium intake was reported to be 342 mg/day 8 . Hence, for some populations such as those of Southeast Asia, supplements represent a suitable dietary source of calcium 9 …”
Section: Introductionmentioning
confidence: 99%
“…Calcium has many benefits, such as lowering blood pressure particularly among young people, hypertensive disorders of pregnancy, prevention of osteoporosis and colorectal adenomas, lowering blood pressure in the progeny of mothers talking sufficient calcium during pregnancy and lowering cholesterol values (Cormick and Belizan, 2019). It is important nutrient to maximize peak bone mass for osteoporosis prevention (Marcinow et al, 2017) and also effective on non skeletal, especially cardiovascular (Tankeu et al, 2017).…”
Section: Introiductionmentioning
confidence: 99%